Emotional intelligence measures for concept car design in Malaysia - Abdul Kadir., Andi Nursyuhada (2023)
Malaysia introduces several National Plans and Policies from an Industrial Design perspective as an effort for The Agenda 2030 on Sustainable Development Goals (SDGs) such as the Industry4WRD, National Transport Policy (NTP), and National Automotive Policy (NAP). All these policies emphasize smart culture and human well-being by adapting technology to human nature. High technology versus human value has become the main issue for the Malaysia Road Safety Plan (MRSP) since the fatality rate still concerning due to contemplating between technology usage and relying on smart technology during driving to combat these issues or otherwise. The exploration of this matter may be seen through Concept Car Design (CCD), with Artificial Intelligence (AI) implementation in the automotive industry beginning to introduce innovations like voice command and face recognition making futuristic concept cars growing rapidly. These cars are positioned as Emotional Intelligence (EI) cars, smart enough to understand user emotions, safe, and more convenient mobility experience. However, whether these concepts are viable is still extensively unexplored. Hence, the study aims to identify EI measures for CCD in Malaysia. Two phases of research design were proposed in this study. In Phase One, the Repertory Grid Technique (RGT) was used to understand how ten automotive designers perceive EI by comparing six of the selected concept cars (elements) and successfully elicited ten bipolar poles (constructs) of AI and EI. It was then rated with a scale of one to five in the grid form and analyzed using OpenRepGrid to explore the descriptive statistics, correlations, root mean square, and the visualization plot of the elements and constructs. As the results, EI measures on BMW Concept (M=3.4; SD=1.71), MINI Concept (M=3.0; SD=1.76), and Rolls Royce Concept (M=3.0; SD=2.11) presented the highest mean of (n=10) and all positively correlated (r = 0.96), extruded Emotional Intelligence with Conceptual Images, More Informative, Simple Interaction, Homelike, High Autonomous, Multipurpose Drive, Luxury, User-Friendly Application, and Leisure. The continuation of the study used these three elements of the concept cars as stimuli in Phase Two of the Electroencephalogram (EEG) and Virtual Reality (VR) experiment. The experiment purposely analyzes the emotions of twenty subjects on CCD using sixteen channels of brain signal while using VR which consists of Video One (Current car accident experience) and Video Two (Concept Car - EI measures). MATLAB with the Mel Frequency Cepstral Coefficients (MFCC) for feature extraction and Multilayer Perception (MLP) as classifier used to analyze the Valence and Arousal emotions (Happy, Calm Fear, Sad). Most subjects started with negative emotions and turned positive after experiencing Video Two on the concept car. The results show the need for EI exploration and conclude EI measures as EI=User Experience (UX) + User Interface (UI) that create emotional connection, adapt user emotion, and enable better interaction are things to consider for EI measures for CCD in Malaysia. Indirectly, this contributes to the Next Generation Vehicle NAP National Plan and the future bridge of multidisciplinary studies to embark on life and emotion concerns.